PENGARUH VARIABEL EKONOMI MAKRO TERHADAP NILAI TUKAR RUPIAH - Ratna Christianingrum (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2019)
Exchange rate is an important economic indicator that has a strategic role in economy. Exchange rate movement widely influence various aspects of economy. In the efforts to maintain the exchange rate stability, recognizing the factors affecting the movements is required. This research is conducted to analyze the influence of interest rate, exchange reseve, money supply, balance of payment and inflation rate to rupiah exchange rate. Data analysis was done by using Vector Error Correction Models (VECM). The result show that in short-run Bank Indonesia rate and money supply have a significant effect to rupiah exchange rate. In long-run Bank Indonesia rate, money supply, balance of payment and inflation rate have a significant effect to rupiah exchange rate.